Contribution to the knowledge of the Afrotropical Evonima Walker, 1865 generic complex with description of two new genera and two new species (Lepidoptera: Nolidae, Nolinae) - Gy. M. László (SHILAP, 2020)
The generic assignment of the African taxa of the genus Evonima Walker, 1865 is revised. Based on diagnostic characters of the male genitalia structure, a new genus Vansonima László, gen. n. is erected for E. littoralis (van Son, 1933) and E. ruhija Hacker, 2012. A further new genus, Laetonima László, gen. n. is established for two undescribed species reminiscent externally of Evonima, which are also described here as new to science: L. smithi László, sp. n. and L. camerunica László. sp. n. Consequently, E. westafricana Hacker, 2012 is the only known true Evonima species occurring in Africa. The female genitalia of E. westafricana is described and illustrated here for the first time. New distribution records of E. westafricana and V. littoralis abyssinica (Hacker, 2012) are provided together with 14 colour and 9 black and white figures.